An efficient two-factor user authentication scheme with unlinkability for wireless sensor networks - Jiang, Qi; Ma, Jianfeng; Lu, Xiang; Tian, Youliang (Peer-to-peer networking and applications, 2015)
User authentication with unlinkability is one of the corner stone services for many security and privacy services which are required to secure communications in wireless sensor networks (WSNs). Recently, Xue et al. proposed a temporal-credential-based mutual authentication and key agreement scheme for WSNs, and claimed that their scheme achieves identity and password protection, and the resiliency of stolen smart card attacks. However, we observe that Xue et al.’s scheme is subject to identity guessing attack, tracking attack, privileged insider attack and weak stolen smart card attack. In order to fix the drawbacks, we propose an enhanced authentication scheme with unlinkability. Additionally, the proposed scheme further cuts the computational cost. Therefore, the proposed scheme not only remedies its security flaws but also improves its performance. It is more suitable for practical applications of WSNs than Xue et al.’s scheme.